2002
DOI: 10.1103/physrevlett.88.157002
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure ofMgB2from Angle-Resolved Photoemission Spectroscopy

Abstract: The first angle-resolved photoemission spectroscopy results from MgB2 single crystals are reported. Along the GammaK and GammaM directions, we observed three distinct dispersive features approaching the Fermi energy. These can be assigned to the theoretically predicted sigma (B 2p(x,y)) and pi (B 2p(z)) bands. In addition, a small parabolic-like band is detected around the Gamma point, which can be attributed to a surface-derived state. The overall agreement between our results and the band calculations sugges… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
57
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 30 publications
13
57
1
Order By: Relevance
“…Further research has found that MgB 2 exhibits a rich multiple-band structure, which has been observed by a number of experimental techniques, such as angleresolved photoemission spectroscopy, the de Haas-van Alphen effect, and the Hall resistivity. [5][6][7] These results confirm previous band structure calculations 8,9 and reveal strongly two-dimensional sp x p y ͑ ͒ bands, as well as threedimensional p z ͑ ͒ bands. Owing to the simple hexagonal structure ͑space group P6 / mmm͒, four optical modes at the G point of the Brillouin zone are predicted for MgB 2 : a silent B 1g mode ͑at 87.1 meV, Ϸ700 cm −1 ͒, the E 2g Raman mode ͑at 74.5 meV, Ϸ600 cm −1 ͒, and the infrared active E 2u ͑at 40.7 meV, Ϸ330 cm −1 ͒, and A 2u ͑at 49.8 meV, Ϸ400 cm −1 ͒ modes, where only the E 2g mode is Raman active and strong coupling to the electronic conduction bands is predicted.…”
Section: Introductionsupporting
confidence: 80%
“…Further research has found that MgB 2 exhibits a rich multiple-band structure, which has been observed by a number of experimental techniques, such as angleresolved photoemission spectroscopy, the de Haas-van Alphen effect, and the Hall resistivity. [5][6][7] These results confirm previous band structure calculations 8,9 and reveal strongly two-dimensional sp x p y ͑ ͒ bands, as well as threedimensional p z ͑ ͒ bands. Owing to the simple hexagonal structure ͑space group P6 / mmm͒, four optical modes at the G point of the Brillouin zone are predicted for MgB 2 : a silent B 1g mode ͑at 87.1 meV, Ϸ700 cm −1 ͒, the E 2g Raman mode ͑at 74.5 meV, Ϸ600 cm −1 ͒, and the infrared active E 2u ͑at 40.7 meV, Ϸ330 cm −1 ͒, and A 2u ͑at 49.8 meV, Ϸ400 cm −1 ͒ modes, where only the E 2g mode is Raman active and strong coupling to the electronic conduction bands is predicted.…”
Section: Introductionsupporting
confidence: 80%
“…There is a finite coupling between the π and σ bands, and both gaps vanish at a common T c . Besides the two widely observed gaps [9][10][11][12] , first-principles calculations taking into account the fully anisotropic electron-phonon interaction predict that there should also be an intraband anisotropy within the σ and π gaps 1,2 . In an earlier work Choi et al solved the Eliashberg equation in the clean limit, using an anisotropic electron-phonon interaction λ(k,k′), and found an energy gap ∆(k) that spreads between 1.2 and 3.7 meV for the π bands and from 6.4 to 7.2 meV for the σ bands 1,13 .…”
mentioning
confidence: 99%
“…MgB 2 15-20 is a notable exception: it is a layered material with multigap, phonon-mediated superconductivity at T c = 39K with some quasi-two-dimensional bands, making it an ideal candidate to study the temperature dependence of the dispersion renormalization due to electron-phonon coupling. LDA calculations 17 predict four bands crossing Fermi level in MgB 2 : two quasi 2D σ-bands from p x , p y orbitals around Γ and two 3D π-bands from p z orbital 27,31,32 . The superconductivity is believed to caused by the E 2g phonon mode at 75meV that couples strongly to the 2D σ-bands, but more weakly to the π-bands 19 , leading to two different gaps, ∆ σ = 6.5 meV and ∆ π = 1.5meV, as revealed by previous tunneling 26 and ARPES studies 27 .…”
mentioning
confidence: 99%